COVAX and the rise of the 'super public private partnership' for global health - Katerini Tagmatarchi Storeng; Antoine de Bengy Puyvallée; Felix Stein (Taylor & Francis Group, 2023)
ABSTRACTCOVAX, the vaccines pillar of the Access to Covid-19 Tools Accelerator (ACT-A), has been promoted as 'the only global solution' to vaccine equity and ending the Covid-19 pandemic. ACT-A and COVAX build on the public-private partnership (PPP) model that dominates global health governance, but take it to a new level, constituting an experimental form that we call the 'super-PPP'. Based on an analysis of COVAX's governance structure and its difficulties in achieving its aims, we identify several features of the super-PPP model. First, it aims to coordinate the fragmented global health field by bringing together existing PPPs in an extraordinarily complex Russian Matryoshka doll-like structure. Second, it attempts to scale up a governance model designed for donor-dependent countries to tackle a health crisis affecting the entire world, pitting it against the self-interest of its wealthiest government partners. Third, the super-PPP's structural complexity obscures the vast differences between constituent partners, giving pharmaceutical corporations substantial power and making public representation, transparency, and accountability elusive. As a super-PPP, COVAX reproduces and amplifies challenges associated with the established PPPs it incorporates. COVAX's limited success has sparked a crisis of legitimacy for the voluntary, charity-based partnership model in global health, raising questions about its future.